PENERAPAN MOTIF NUSANTARA DALAM PENCIPTAAN KARYA BATIK DI CV. TARUM BALI SEJAHTERA - Nurlaeli Dwi Safitri; Ni Kadek Karuni; Ida Ayu Gede Artayani (Pusat Penerbitan LP2MPP ISI Denpasar, 2022)
Internship / work practice is a practical activity for students with the aim of gaining experience from these activities, which can later be used as a professional development for students. This activity is carried out directly in the world of work for real. As for this internship activity the creator does on the CV. Tarum Bali Sejahtera in Gianyar Bali.This place of business is dabbling in textiles, especially batik and natural coloring. The method of creation used in the creation of the work of this apprenticeship process is through two approaches intuitively, and through carefully planned, analytical and systematic scientific methods. In the method refers to the theory of creation proposed by SP. Gustami in his book entitled